2002
DOI: 10.2174/1568010023344607
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Gene Transcription in Asthma and Chronic Obstructive Pulmonary Disease: Antioxidant Therapeutic Targets

Abstract: Inflammatory lung diseases such as asthma and Chronic Obstructive Pulmonary Disease (COPD) are characterised by systemic and local chronic inflammation and oxidative stress. The sources of the increased oxidative stress in patients with asthma and COPD derive from the increased burden of inhaled oxidants, and from the increased amounts of reactive oxygen species (ROS) generated by several inflammatory, immune and structural cells of the airways. Increased levels of ROS produced in the airways are reflected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 212 publications
(317 reference statements)
2
71
0
4
Order By: Relevance
“…Several studies have reported that the magnitude of oxidative stress in COPD is greater than that in asthma [43][44][45][46][47][48][49]. Similar findings were reported in rheumatoid arthritis patients, in whom oxidative stress was correlated with MSI in synovial tissue [32].…”
Section: Discussionsupporting
confidence: 54%
“…Several studies have reported that the magnitude of oxidative stress in COPD is greater than that in asthma [43][44][45][46][47][48][49]. Similar findings were reported in rheumatoid arthritis patients, in whom oxidative stress was correlated with MSI in synovial tissue [32].…”
Section: Discussionsupporting
confidence: 54%
“…The mechanism why MG132 induces activation of these kinases is not well elucidated. ROS production served as a pivotal linkage in enhancing the proinflammatory gene expression through the activation of stress kinases (JNK, MAPK, p38, PI3K/Akt; Rahman, 2002). Here, we found that MG132 indeed elevated intracellular ROS production.…”
Section: Discussionmentioning
confidence: 50%
“…Regulation of proinflammatory gene expressions by ROSdependent signaling pathways had been reported (Rahman, 2002). We tested whether proteasome inhibitor-induced COX-2 expression was involved ROS; hence two ROS scavengers, NAC and GSH, were used.…”
Section: Inhibition Of Mg132-induced Cox-2 Expression Ros Productionmentioning
confidence: 99%
“…In acute and chronic inflammation, the production of ROS increases at a rate that overwhelms the capacity of the endogenous defense system to remove them (40). Moreover, GSH is an important component of the lung antioxidant defense (41). Therefore, a supplementation of this antioxidant agent is necessary to protect lungs from oxidative stress during acute or chronic inflammation.…”
Section: Pulmonary Veinsmentioning
confidence: 99%